Analisa Unifi Controller dan MikroTik RouterOS pada Wireless Local Area Network - Rahman, Taufik; Kuswanto, Herman; Saputra, Elin Panca (SemanTIK : Teknik Informasi, 2024)
The integration of smart access points such as Unifi Access Point (UAP) with the UnifiOs system to enhance the performance and reliability of wireless networks. In this context, the main issue is the lack of integration between conventional access points and management systems, resulting in ineffective monitoring and management of networks and connected devices. Configuration and integration between the Unifi Controller and MikroTik RouterOS in the topology are used to facilitate network management more effectively. By using the Unifi Controller as the convergence point for VLAN networks from the MikroTik router, different subnetworks can be integrated and distributed through Unifi Access Points. Throughput testing shows a data delivery rate of 46 kilobytes per second, while packet loss testing indicates high reliability, with data being transmitted without loss. The findings of this research provide a strong foundation for meeting the demands of performance and reliability in wireless networks across various environments, from personal to complex business scales.